Spelling in developmental dyslexia in Chinese: Evidence of deficits in statistical learning and over-reliance on phonology. Issue 7 (16th November 2020) - Lee, Stephen Man Kit; Tong, Xiuli
ABSTRACT: This study employed a multi-dimensional (i.e., orthographic, phonological, and semantic) and bi-level (i.e., character and radical) approach to analyze the character writing of 120 Hong Kong Chinese children with developmental dyslexia in Grades 2–5 and 120 typically developing age-matched controls. Relative to their typically developing peers, children with dyslexia were less sensitive to the positional and functional consistencies of sublexical radicals and exhibited prolonged use of phonology at the character level as grade-level advanced. Furthermore, the children with dyslexia relatively relied more on phonology at the radical level than younger, reading level-matched children. These results indicate the effects of implicit statistical learning on the development of Chinese character writing skills and suggest that the prolonged use and overreliance on phonology in character writing by Chinese children with dyslexia may reflect their difficulties in implicit statistical learning.